A Narrative review of exercise and metabolic disease of the heart - Liao, Da-Ming; Chen, Chieh (Journal of Cardiovascular Medicine and Cardiology, 2023)
According to the WHO’s report, the number of people with diabetes worldwide is increasing, and the prevalence of type 2 diabetes in adults who is over 18 years old has risen from 4.7% in the 1980s to 8.5% in 2014. Among them, the prevalence of diabetes in low- and middle-income countries has even reached as high as 9.3% over the decades. Metabolic-Associated Fatty Liver Disease (MAFLD) is not only affecting the liver but is also considered a problem for the heart, as there is about 25% of the patients suffer from the cardiovascular syndrome. Around the world, the elderly population is growing rapidly. The elderly population is growing faster than expected, with Taiwan becoming an aged society in 2018. One of the health issues associated with aging is the population with cardiovascular disease increases. Patient care may result in huge expenditures on the national economy, society, family care, medical resources, and drugs. This article adopts perspectives from literature reviews using databases such as Cochrane Library, PubMed (Medline), Up-to-date and Google scholar using three main methods: search for keywords cardiovascular disease, physical fitness, exercise prescription intervention, quality of life, cardio metabolic disease, etc.; search for related articles on physical activity and cardiovascular disease, neuroendocrine, molecular biology, etc.; combined with case-control studies, systematic review and meta-analysis, analytical research, and randomized control studies to explore the effects of physical activity intervention and the fitness level of the elderly on the epidemiology of the cardiovascular disease, prevention of cardio metabolic disease, improvement of quality of life. Understanding which types of exercise intervention help improve the quality of life of patients with cardiovascular disease. This article aims to propose exercise prescriptions for physical fitness to prevent cardiovascular disease; be used as a reference for health promotion in the world, provide guidance on cardiovascular disease prevention and cardiovascular disease care for the elderly, and construct guidelines on physical fitness and exercise prescriptions in Taiwan.